Disseminated granuloma annulare: A cutaneous adverse effect of anti-TNF agents - Mondhipa Ratnarathorn; Siba P Raychaudhuri; Stanley Naguwa (Indian Journal of Dermatology, 2011)
Tumor necrosis factor-alpha (TNF-α) inhibitors, such as etanercept, infliximab, and adalimumab, bind to TNF-α and thereby act as anti-inflammatory agents. This group of drugs has been approved for the treatment of rheumatoid arthritis, psoriatic arthritis, moderate to severe plaque psoriasis, ankylosing spodylitis, Crohn disease, and juvenile idiopathic arthritis. We describe a 56-year-old woman who developed an erythematous pruritic rash on both arms-diagnosed as granuloma annulare by skin biopsy-approximately 22 months after initiating adalimumab for treatment of rheumatoid arthritis. On stopping adalimumab there was total clearance of the skin lesions, but a similar rash developed again when her treatment was switched to another anti-TNF agent (etanercept). This clinical observation supports a link between TNF inhibition and the development of granuloma annulare.